2021
DOI: 10.1016/j.celrep.2021.109320
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells targeting SARS-CoV-2 spike protein and their dependence on CD4+ T cell help

Abstract: Memory B cells seem to be more durable than antibodies and thus crucial for the long-term immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Here we investigate SARS-CoV-2 spike-specific memory B cells and their dependence on CD4 + T cell help in different settings of coronavirus disease 2019 . Compared with severely ill individuals, those who recovered from mild COVID-19 develop fewer but functionally superior spike-specific memory B cells. Generation and affinity maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 26 publications
6
51
1
Order By: Relevance
“…Though negative with RT-PCR, the NP individual laboratory parameters unveiled an evolved inflammatory state in which immune alterations were somehow more stable. The prevalence of an inverted CD4/CD8 ratio increasing with age and the presence of metabolic disorders such as DM2, hypertension, overweight, and kidney and heart diseases [28,29,[33][34][35]43,45,46,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though negative with RT-PCR, the NP individual laboratory parameters unveiled an evolved inflammatory state in which immune alterations were somehow more stable. The prevalence of an inverted CD4/CD8 ratio increasing with age and the presence of metabolic disorders such as DM2, hypertension, overweight, and kidney and heart diseases [28,29,[33][34][35]43,45,46,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…However, regardless the quantity of circulating antibodies, the occurrence of memory T cells and B-lymphocytes due to SARS-CoV-2 stimulation is crucial for long-term immunity. In this scenario, the attendance of active T helper cells is suggestive of normal configurations of humoral immune response and the formation of specific memory B cell clusters capable of initiating responses against further reinfection [16,23,24,[29][30][31][32][33][34][35][36][37][38][39]. Indeed, the presence of neutralizing antibodies has been revealed to be a good resource to control SARS-CoV2 infection either in vitro or in vivo, though not all patients who recover from COVID-19 show enough neutralizing antibodies to be used as anti-COVID-19 therapy, suggesting a complex relationship between humoral and cellular response in COVID-19 pathogenesis [30][31][32][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of SARS-CoV-2-specific CD4 + T cells or CCR6 − peripheral Tfh cells in COVID-19 patients has been shown to correlate with virus-neutralizing antibody levels [143,144]. In addition, it has been reported that spike protein-specific memory B cell differentiation and antibody affinity maturation in mildly recovered COVID-19 and severely ill patients correlate well with the function of IL-21-producing CD4 + T cells [145]. These results show that in SARS-CoV-2 infection, similar to other viral infections, Tfh cellinduced IL-21-mediated germinal center B cell differentiation is crucial for the production of useful virus-neutralizing antibodies.…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%
“…The cells intake the lipid nanoparticles, which allows the COVID-19 spike protein to be synthesized in the cells. The COVID-19 spike protein can then be presented to CD4+ T cells once they are processed, and the cells then convert into memory T cells, and CD4 T cells aid B cells with the conversion into plasmocytes, which allows the production of antibodies [150,151].…”
Section: Technological and Dosage Regimen Of Current Covid-19 Vaccinesmentioning
confidence: 99%